Ibuprofen Use Did Not Affect Outcome Metrics After Arthroscopic Rotator Cuff Repair, - Nicholas R. Kraus, M.S., B.A; Kirsten D. Garvey, M.S., B.A; Laurence D. Higgins, M.D., M.B.A; Elizabeth Matzkin, M.D (Elsevier, 2021)
Purpose: To determine whether patients who are prescribed ibuprofen after arthroscopic rotator cuff repair have significantly different patient-reported outcomes for pain, function, and overall health at baseline and 1 and 2 years after operation relative to patients only prescribed opioids. Methods: Patients who underwent a rotator cuff repair by a total of 3 surgeons and participated in the outcomes registry from 2012 to 2016 were screened for inclusion in this study. Inclusion criteria were primary arthroscopic rotator cuff repair, at least 2 years from the date of surgery and over the age of 18. Exclusion criteria were revision and open rotator cuff repair. All patients followed the standard postoperative rehabilitation protocol for rotator cuff repair. Patients were divided into 2 cohorts. Group I included patients who received ibuprofen/nonsteroidal anti-inflammatory agents (NSAID) after surgery (n = 281), and Group II consisted of patients who did not receive ibuprofen/NSAID after surgery (n = 182). Patient-reported outcome measures for Visual Analogue Scale, American Shoulder Elbow Surgeons score, Single Assessment Numeric Evaluation score, Simple Shoulder Test and The Veterans Rand 12-Item Health Survey were collected preoperatively and at 3 and 6 months, 1 year, and 2 years after surgery. Statistical analysis was performed to compare patient-reported outcome measures between Group I and II. Results: This study consisted of 463 patients who underwent arthroscopic rotator cuff repair, and patients were divided into 2 cohorts. There were 281 patients who did not receive ibuprofen/NSAID after operation in Group I and 182 patients who did receive ibuprofen in Group II. There were no statistically significant differences between the 2 groups in age at treatment, mean body mass index, gender, ethnicity, diabetes, and number of rotator cuff tendons involved; however, there was a statistically significant difference in receiving worker's compensation (P = .005), and this was subsequently adjusted for in our analysis. There were no significant differences in patient-reported outcomes for all metrics between the group prescribed ibuprofen and the group that was not prescribed ibuprofen at 1 and 2 years after surgery or in change from baseline. Conclusion: Patients receiving ibuprofen did as well as patients who did not receive ibuprofen after arthroscopic rotator cuff repair on patient-reported outcome measures assessing shoulder pain, function, and overall health. Level of Evidence: Level III, retrospective comparative study.